The relationships between rugby players’ tackle training attitudes and behaviour and their match tackle attitudes and behaviour - Hendricks, Sharief (BMJ Open Sport Exerc Med, 2015)
BACKGROUND: The tackle event in rugby is a technical and physical contest between opposing players. A player's ability to tolerate and contest during a tackle is a prerequisite for safe participation and success in rugby. Little is known about the relationship between tackle training and tackling in matches in rugby union. Therefore, we investigated the relationships between players’ training attitudes and behaviour and their match attitudes and behaviour for tackling in rugby union. METHOD: A questionnaire was designed to assess attitude (importance) and behaviours (frequency and quantity) among junior (under 19) players on a 5-point Likert Scale. Questionnaires were handed out to 220 players (10 schools) at a tournament and 75% (9 schools, n=164) were returned for analysis. Associations between training attitudes and behaviours were tested using the χ(2) test, Cramer's V and τ-b. RESULTS: The more time spent on emphasising proper technique to prevent injuries in training, the more important players rated ‘own safety’ (τ-b=0.21, moderate, z=3.1, p<0.01), ‘going for the ball only’ (τ-b=0.27, moderate, z=4.6, p<0.001) and ‘staying on feet’ (τ-b=0.23, moderate, z=3.6, p<0.001) in match play. The more time spent on emphasising proper technique to improve performance in training, the more important players rated actions ‘going for ball only’ (τ-b=0.23, moderate, z=3.7, p<0.001) and ‘preventing the ball carrier from retaining position’ (τ-b=0.20, moderate, z=3.1, p<0.01) in match play. CONCLUSIONS: This is the first study to report on the relationships between players’ training attitudes and behaviour and their match attitudes and behaviours for tackling in rugby union. The importance of tackle training to prevent injury, and the amount of time spent on technique to prevent injuries, was associated with behaviours that reduce the risk of injury in matches.